New Eremidrilus species (Clitellata: Lumbriculidae) from western North America. Part 1, species with two spermathecal segments - Fend, Steven; Rodriguez, Pilar (Zootaxa, 2020)
Four new species of the lumbriculid genus Eremidrilus Fend & Rodriguez, 2003 are described from Idaho, Montana, and New Mexico. The new species all have a filiform proboscis, club-shaped atria in X, each with two functional vasa deferentia, and spermathecae paired in both XI and XII. Male pores of Eremidrilus artzaini n. sp., E. humboldti n. sp., and E. gilita n. sp. are all associated with distinctive porophores, but these structures are absent in E. montanensis n. sp. The new species are easily distinguished from California Eremidrilus species, all of which have spermathecae only in XI. New observations of type specimens of Eremidrilus allegheniensis (Cook, 1971), a species with two spermathecal segments, known only from eastern USA, confirm differences in atrial morphology, and also document unusual spermathecal porophores and ventral glands.